O MUNICÍPIO E A CONSTRUÇÃO DA POLÍTICA LOCAL DE EDUCAÇÃO: ESTUDO DE CASO NUMA AUTARQUIA DO OESTE - António Francisco Baixinho (EccoS – Revista Científica)
This article is an empirical research, carried out under the Specialization Course in Educational Administration and focused on a small town in Western Region of Portugal, on how the policy is built of local education. Assuming the research approach of a qualitative nature, it was known as are performed by township legal skills in education. As well as learn about the situation regarding the existence of the Municipal Council of Education, the involvement of social partners in education, school-municipality relations, the existence of a local educational project, the intervention of the municipality building in the territories and educational projects for socio-education developed by the municipality. ¿In a purported edu-educational framework of decentralization of powers to local authorities, the charter school, has not yet been drafted (at the time of the study) and the council is conditioned on the performance of its duties and responsibilities by some legal constraints.